Urban Community Environmental Quality Assessment and Improvement Plan Based on Statistical Analysis and Optimization Algorithms - Po Kevin, Wu Kwai (International Journal of Computer Science and Information Technology, 2024)
Urban environmental pollution, including air and noise pollution, affects the lives of millions of people in cities around the world prematurely dying because of respiratory and cardiovascular disease. The approach of this study is to apply statistical analysis and optimization algorithms in tandem for assessing and upgrading the quality of urban environment as a unique way of managing pollution in an evolving urban system. We conducted a cross-sectional design using air quality monitoring stations, community health surveys and remote sensing data. Correlations among pollutants and health outcomes were tested using the aid of statistical models. In this work optimization algorithms were incorporated with GA and SVR, used as an effective tools to synthesize feasible pollution control strategies. Treatment with various NRTIs i.e T, Z and H in 1–24 h significantly induced TNFα followed by IFNγ in serum which were strongly related to each other (r~0.9) as well as their initial presence was directly proportional with the dose (treated), endorsing a positive dose-dependent response inducing inflammation of all treated patients up to minimum during that early period meanwhile no significant changes were observed for control or placebo group. 5 receive a much lower coefficient of 0.72 for air which relates to both respiratory diseases (Table 4). The PM2. 5 levels decreased respiratory disease cases by 18% in high-pollution areas over a six-month time period. It is clear that the findings are consistent with past literate about urban pollutants negatively impacting human health, however the study offers a new perspective on the issue via optimization algorithms. Because the study is of a cross-sectional design, it can only suggest that tailored emission control plans could substantially foster community health, instead of demonstrating causal inference. Subsequent Confirmatory research has discussed the need for longitudinal studies and suggested the use of machine learning algorithms to perform real-time assessments.